The effect of acute stretching on agility performance - van Gelder, L. H.; Bartz, S. D. (The Journal of Strength and Conditioning Research, 2011)
Static stretching (SS) has shown decreases in many areas including strength, anaerobic power, and sprinting time. Dynamic stretching (DS) has shown increases in anaerobic power and decreases in sprinting time. Research on the effects of stretching on agility performance is limited. The purpose of this study was to determine the effect of SS and DS on performance time of a sport agility test. Sixty male subjects consisting of collegiate (n = 18) and recreational (n = 42) basketball athletes volunteered for the study. Subjects were randomly assigned to 1 of 3 intervention groups: SS, DS, or no stretching (NS). All groups completed a 10-minute warm-up jog followed by a 3-minute rest. The SS and DS groups then completed an 8.5-minute stretching intervention. Next, all subjects completed 3 trials of the 505 agility test with 2-5 minutes of rest between trials. A 2-way repeated-measure analysis of variance (Stretch group, athlete category, group × athlete interaction) was used to determine statistical significance (p < 0.05). A Tukey post hoc test was performed to determine differences between groups. For all athletes, the DS group produced significantly faster times on the agility test (2.22 ± 0.12 seconds, mean ± SD) in comparison to both the SS group (2.33 ± 0.15 seconds, p = 0.013) and NS group (2.32 ± 0.12 seconds, p = 0.026). Differences between the SS and NS groups revealed no significance (p = 0.962). There was a significant difference in mean times for the type of athlete (p = 0.002); however, interaction between the type of athlete and stretching group was not significant (p = 0.520). These results indicate that in comparison to SS or NS, DS significantly improves performance on closed agility skills involving a 180° change of direction.